Assessment of external radiation dose rate after 18FDG-PET/CT examination - Hanan Aldousari; Nouf Abuhadi; Mariam Izz; Thekra Alshammari; Zainab Ali; Razan Aldaas; Abdoelrahman Hassan Ali Bakry; Ahmed Abukonna; Abdulredha Esmail (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background F-18 FDG (fluorodeoxyglucose) PET/CT procedures are one of the most growing studies used for patient management in oncology, cardiology, neurology, and other indications, in which the challenges meet both patients and clinicians, especially when we are looking for the presence/absence of disease progression and cure. This study was conducted to assess the external radiation dose after 18FDG-PET/CT examination. In total, 117 patients were enrolled in the study. Radiation exposure was measured using a calibrated RadEye SPRD-ER personal radiation detector. The measurements were taken at 0, 30, 100, 150, and 200 cm distance from the patient. The time of measurement was immediately post-injection, 30 min, 60 min after injection, and at the time of releasing the patient. Results The result showed that the mean radiation equivalent dose rate at 0 min/0 cm was 414 µSv/h, at 30 min/30 cm was 99.7 µSv/h, and 60 min/100 cm was 18.3 µSv/h. The radiation doses at different distances (0, 30, 100, 150, and 200 cm) were 160.9 µSv/h, 70.9 µSv/h, 12.4 µSv/h, 7 µSv/h, and 3.7 µSv/h, respectively. Conclusion In conclusion, the patient can be safely released after 2 h of injection in (18F-FDG) PET/CT and the radiation dose can be limited by increasing distance from the radiation source and also instructing them to drink much more water to enhance the process of excretions. The dose rates are low in this study; if the staff interact with multiple patients, they will not approach exposure limits. Similarly, dose rates are so low at patient release that family will not receive doses above regulatory limits.